2014
DOI: 10.1016/j.pocean.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variability of the siphonophores Muggiaea atlantica and M. kochi in the Western English Channel

Abstract: a b s t r a c tWe investigated long-term variability of the calycophoran siphonophores Muggiaea atlantica and Muggiaea kochi in the Western English Channel (WEC) between 1930 and 2011. Our aims were to describe long-term changes in abundance and temporal distribution in relation to local environmental dynamics. In order to better understand mechanisms that regulate the species' populations, we identified periods that were characteristic of in situ population growth and the environmental optima associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 64 publications
(110 reference statements)
2
28
0
1
Order By: Relevance
“…Our results support this hypothesis and suggest a critical basal limit of 10°C for asexual reproductive activity of M. atlantica in the Western English Channel. This thermal limit is in agreement with the results of Blackett et al (2014) who showed that local development of the M. atlan ti ca polygastric population at an open-shelf station in the Western English Channel only occurred when the sea surface temperature was above 9°C.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results support this hypothesis and suggest a critical basal limit of 10°C for asexual reproductive activity of M. atlantica in the Western English Channel. This thermal limit is in agreement with the results of Blackett et al (2014) who showed that local development of the M. atlan ti ca polygastric population at an open-shelf station in the Western English Channel only occurred when the sea surface temperature was above 9°C.…”
Section: Discussionsupporting
confidence: 92%
“…However, recurrent reproductive activity in winter would appear unlikely given that the winter temperatures typically experienced are below the thermal tolerances of M. atlantica discussed above. The M. atlantica population in the Western English Channel likely represents the northern component of a spatially extensive Northeast Atlantic metapopulation (Blackett et al 2014). Pulses of winter abundance observed in the present study could thus indicate immigration from a sub-population located to the south, probably within the Bay of Biscay (reviewed in Mackie et al 1987).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In particular, when the front occurred over the shelf in early June, salinity was the variable most strongly related to the spatial distributions of both species (Tables 3 and 4). Salinity has previously been reported as a determinant factor for the distributions and abundance of gelatinous zooplankton at various locations in the NW Mediterranean (Gili et al 1988, Licandro et al 2012) and the North Atlantic (Blackett et al 2014, Greer et al 2015.…”
Section: Discussionmentioning
confidence: 95%
“…The gelatinous zooplankton followed a similar trend, varying in their spatial distributions at short time scales. The two cnidarian species studied are epipelagic, mainly occurring in the surface layer between 0 and 50 m (Gili et al 1987a, b), and holoplanktonic, making them particularly susceptible to surface-water dynamics (Mackie et al 1987, Blackett et al 2014.…”
Section: Discussionmentioning
confidence: 99%